Arti Penting Mata Uang Cryptocurrency Sebagai Alat Pembayaran Yang Sah Menurut Prefektif Hukum Indonesia Di Era Revolusi Industri 4.0 - Donny Raynaldo Tungkiman (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2021)
In the era of the industrial revolution 4.0 today, many people make this cryptocurrency as an investment and even become a legal payment in several developed countries in the world. However, Cryptocurrency is also widely associated with attractive investments where the Cryptocurrency exchange rate is relatively higher in percentage in this current era. But in the legal perspective in the State of Indonesia, Bank Indonesia refuses to deal with legal payments related to Cryptocurrency which cannot be used as a medium of exchange for any goods or services. In addition, according to Bank Indonesia, it is vulnerable to hacking related to cryptocurrencies and triggers related to money laundering and terrorism financing. This makes Indonesia refuse to use Cryptocurrencies as legal tender. However, with such thoroughness the discussion is still not perfect, because one of the characteristics of laws and regulations is that they are flexible and dynamic in following the development of society. Therefore, in the era of the industrial revolution 4.0, you must keep up with the times so you don't get left behind. But in this case, actually, legalizing Cryptocurrency in Indonesia can improve economic standards in Indonesia. Keywords: Cryptocurrency, currency, Indonesian bank, means of payment.